Metaphor in discourse - Semino, Elena (Cambridge University Press, 2008)
Metaphor' is the phenomenon whereby we talk and, potentially, think about something in terms of something else. In this book Elena Semino discusses metaphor as a common linguistic occurrence, which is varied in its textual appearance, versatile in the functions it may perform, and central to many different types of communication, from informal interaction to political speeches. She discusses the use of metaphor across a variety of texts and genres from literature, politics, science, education, advertising and the discourse of mental illness. Each chapter includes detailed case studies focusing on specific texts, from election leaflets to specialist scientific articles. Also included is a detailed consideration of corpus (computer-based) methods of analysis. Wide-ranging and informative, this book will be invaluable to those interested in metaphor from a range of disciplines.